2022
DOI: 10.35172/rvz.2022.v29.652
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Etioepidemiológicos Da Febre Maculosa Brasileira: Revisão Sistemática

Abstract: A Febre Maculosa Brasileira (FMB) é uma zoonose, febril aguda, de gravidade variável, que geralmente se desenvolve em caráter endêmico, com distribuição mundial, causada por bactérias da família Rickettsiaceae, denominadas Rickettsia rickettsii, Rickettsia sp. cepa Mata Atlântica e Rickettsia parkeri (1, 2, 3). O presente estudo foi delineado com o objetivo de realizar uma revisão sistemática da literatura acerca dos aspectos epidemiológicos da febre maculosa brasileira, entre estudos empíricos publicados em p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
1
0
3
Order By: Relevance
“…A systematic review that analyzed the etioepidemiological aspects of BSF from 2003 to 2018 showed that mortality rates from the disease are around 40%, similar to data found between 2018 and 2022. This fact may be associated with several factors, including such as the difficulty of diagnosing and establishing appropriate therapy, due to the fact that it is a disease with non-specific symptoms and lack of knowledge of the population about the disease [9]. Furthermore, the quality of filling in information on notifiable diseases needs to be analyzed in greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review that analyzed the etioepidemiological aspects of BSF from 2003 to 2018 showed that mortality rates from the disease are around 40%, similar to data found between 2018 and 2022. This fact may be associated with several factors, including such as the difficulty of diagnosing and establishing appropriate therapy, due to the fact that it is a disease with non-specific symptoms and lack of knowledge of the population about the disease [9]. Furthermore, the quality of filling in information on notifiable diseases needs to be analyzed in greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…As riquétsias são bactérias gram-negativas pleomórficas intracelulares obrigatórias com predileção por células endoteliais (MORAES-FILHO, 2017). A manutenção desta enfermidade vem sendo associada à interação entre os ectoparasitas e seus hospedeiros, sobretudo os amplificadores da doença (GAVA et al, 2022). Capivaras, gambás, equinos e cães possuem um papel importante na cadeia epidemiológica da doença, pois atuam como um dos principais reservatórios e disseminadores dos carrapatos transmissores da febre maculosa (PAES DE ARAÚJO ET AL., 2016).…”
Section: Introductionunclassified
“…Diante disso, os carrapatos se infectam ao realizarem o repasto sanguíneo de hospedeiros da enfermidade, constituindo-se dessa forma como vetores e principal reservatório natural do agente. Isso se deve à transmissão vertical, transovariana, transestadial e interestadial desses parasitas, permanecendo infectados ao longo de suas vidas, o que favorece a manutenção da riquétsia na natureza (GAVA et al, 2022). Essas características de transmissão, aliada à sua ampla distribuição geográfica e baixa especificidade de hospedeiro, permitem o parasitismo de vários mamíferos, incluindo o homem de forma acidental (ROCHA, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation